The Current State of CSR in the Football Clubs of the Professional Football League in Jordan - Al-Daaja, Yehia; Szabados, György Norbert (Applied Studies in Agribusiness and Commerce, 2018)
Corporate Social Responsibility (CSR) has become a common practice all over the world, however, social responsibility in the field of sport is still a new concept and received a little attention. This study aims to reveal the current state of social responsibility practices among the football clubs of the professional football league in Jordan. A descriptive survey method was used and a questionnaire was designed to collect the required data on three aspects (administrative, financial and CSR programs). The study found that there is a medium degree of availability of the administrative and financial aspects that activate the implementation of the CSR concept. Moreover, the study also revealed a medium degree of availability of the CSR programs offered by the selected clubs. Furthermore, the study proved that the football clubs in Jordan are aware of their social responsibility and recognize their role in the betterment of the society. JEL Classification: C21, D24, Q12